MRI of Breast Lymphoma: A Report of Two Cases with Emphasis on Diffusion Weighted Imaging and Apparent Diffusion Coefficient Value - Marlina Tanty Ramli Hamid; Noor Laily Syakimah Saidi; Fatimah Kamila Abu Bakar; Sharon Tan Ling Ling; Shamsiah Abdul Hamid; Vijayalakshmi Krishnapillai; Nur Aishah Mohd Taib; Kartini Rahmat (Middle East Journal of Cancer, 2019)
Breast lymphoma is a rare neoplasm that accounts for approximately 0.04-0.5% of breast malignancies. Most breast lymphomas are B-cell type non-Hodgkin lymphomas. The imaging features of breast lymphoma on mammography and ultrasound are nonspecific. There have been several reports on magnetic resonance imaging characteristics of breast lymphoma but only few have described features on diffusion weighted imaging. Herein, we describe the magnetic resonance imaging findings, with emphasis on diffusion weighted imaging and the apparent diffusion coefficient sequences, of two cases of breast lymphoma and compare them with the magnetic resonance imaging features reported in the literature.